2022
DOI: 10.1038/s43247-022-00614-3
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous alteration of the Vastitas Borealis Formation at the Tianwen-1 landing site

Abstract: The Vastitas Borealis Formation is a Hesperian-aged sedimentary unit that mainly covers the Martian northern plains. Its environment of formation is uncertain but may be related to an ancient Martian ocean, outflow channel deposits, compaction and drainage activities, or subsurface ice-related processes. Here we investigate the geological evolution of the Vastitas Borealis Formation using geochemical and mineralogical data acquired by the Mars Surface Composition Detector on board the Zhurong rover at the Tian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 68 publications
4
14
0
Order By: Relevance
“…The average compositions of soils and TAR sands presented in this study agree within error with the LIBS results reported by Liu et al. (2022) [ 26 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The average compositions of soils and TAR sands presented in this study agree within error with the LIBS results reported by Liu et al. (2022) [ 26 ].…”
Section: Resultssupporting
confidence: 92%
“…The pulsed tetrorockets excavated the top layer of the regolith under the Tianwen-1 lander and showed the cemented and indurated layer, similar to those observed at the InSight lander site [ 3 ]. These cemented duricrusts potentially indicate brine activity and the presence of hydrated salts, which are consistent with the in situ observations of the Zhurong site [ 13 , 14 , 26 ] and those inferred for the Viking and InSight sites [ 17 , 18 , 20 ]. The intriguing lithified duricrusts have been inferred previously only at the Viking 1 site.…”
Section: Resultssupporting
confidence: 87%
“…The spectral absorptions have been interpreted to re ect the presence of sulfates/silica 14 or allophane/silica 15 . LIBS results indicate that the detected materials are rich in Ca 15 . Here we found that Ca is negatively correlated with Si (Fig.…”
Section: Hydrous Mineral-rich Duricrust At the Zhurong Landing Regionmentioning
confidence: 99%
“…The Chinese Zhurong rover landed in southern Utopia Planitia (25.066°N, 109.925°E), which has been resurfaced during the Amazonian with the formation of distinctive geomorphic features 11 , loose nearsurface material 12,13 , and hydrous minerals 14,15 . Most of the diverse distinctive landforms are thought to be related to a large reservoir of volatiles 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation